Evidence for post-Acadian through Alleghanian deformation in eastern Maine: multiple brittle reactivation of the Norumbega Fault system - Wang, Chunzeng; Ludman, Allan (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT Detailed mapping in eastern and east-central Maine reveals a complex history of multiple brittle reactivations along the Norumbega fault system (NFS) following initial late Acadian (380 Ma) ductile shearing. Three distinct episodes of brittle faulting are now recognized, each characterized by a unique combination of fault kinematics and dynamics. These three events record a previously poorly-known part of northern Appalachian history — the transition from Acadian stress regimes related to one set of plate collisions to Alleghanian stresses associated with very different plate interactions. Although NFS ductile strain was partitioned into three major high-strain zones in eastern Maine, only the central Waite zone experienced significant post-Acadian brittle deformation. The Waite zone is therefore considered the master fault for the brittle reactivations. All post-Acadian redbed exposures are located in the Waite zone, including two new fault-bounded slivers discovered during this study. The first two brittle faulting episodes predated deposition of the post-Acadian redbeds and both involved dextral strike-slip motion although episode 1 also had a significant dip-slip component. Episode 2 was responsible for the formation of the post-Acadian (Carboniferous?) redbed basins, possibly through a pull-apart mechanism. Brittle episodes 1 and 2 probably occurred in late Devonian through Mississippian times. Oblique (reverse-sinistral) faulting during episode 3 deformed the redbeds and is attributed to the Permian Alleghanian orogeny. Paleostress analyses based on abundant outcrop-scale conjugate faults suggest that the maximum principal stress (఼1) for the three brittle episodes rotated counterclockwise from a WNW — ESE orientation during episode 1 to NE — SW for episode 2 and changed to N-S for episode 3.